No difference in anti-spike antibody and surrogate viral neutralization following SARS-CoV-2 booster vaccination in persons with HIV compared to controls (CO-HIV Study) - Kling, Kendall D.; Janulis, Patrick; Demonbreun, Alexis R.; Sancilio, Amelia; Berzins, Baiba; Krueger, Karen; Achenbach, Chad; Price, Rachelle; Sullivan, Margaret; Caputo, Matthew; Hockney, Sara; Zembower, Teresa; et al. (Frontiers in Immunology, 2023)
Background Understanding the immune response to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) vaccination will enable accurate counseling and inform evolving vaccination strategies. Little is known about antibody response following booster vaccination in people living with HIV (PLWH). Methods We enrolled SARS-CoV-2 vaccinated PLWH and controls without HIV in similar proportions based on age and comorbidities. Participants completed surveys on prior SARS-CoV-2 infection, vaccination, and comorbidities, and provided self-collected dried blood spots (DBS). Quantitative anti-spike IgG and surrogate viral neutralization assays targeted wild-type (WT), Delta, and Omicron variants. We also measured quantitative anti-nucleocapsid IgG. The analysis population had received full SARS-CoV-2 vaccination plus one booster dose. Bivariate analyses for continuous outcomes utilized Wilcoxon tests and multivariate analysis used linear models. Results The analysis population comprised 140 PLWH and 75 controls with median age 58 and 55 years, males 95% and 43%, and DBS collection on 112 and 109 days after the last booster dose, respectively. Median CD4 count among PLWH was 760 cells/mm3 and 91% had an undetectable HIV-1 viral load. Considering WT, Delta, and Omicron variants, there was no significant difference in mean quantitative anti-spike IgG between PLWH (3.3, 2.9, 1.8) and controls (3.3, 2.9, 1.8), respectively (p-values=0. 771, 0.920, 0.708). Surrogate viral neutralization responses were similar in PLWH (1.0, 0.9, and 0.4) and controls (1.0, 0.9, 0.5), respectively (p-values=0.594, 0.436, 0.706). Conclusions PLWH whose CD4 counts are well preserved and persons without HIV have similar anti-spike IgG antibody levels and viral neutralization responses after a single SARS-CoV-2 booster vaccination.